Investigation on the situation of hospital accompanying visitors and patient satisfaction under the nursing management in orthopedic wards in the post-epidemic era (后疫情时代骨科病房护理管理下住院患者探陪现状及满意度调查) - CHEN Liping (陈丽萍); WANG Fengmei (王凤美); LI Nannan (李南南); LI Jing (李靖) (中西医结合护理)
Objective To investigate the situation of hospital accompanying visitors and patient satisfaction under the nursing management of orthopedic wards in the post-epidemic era, in order to provide a reference for how to take into account the needs of patients for visits under the current situation, and to improve the satisfaction of patients and the safe development of medical work. Methods The general situation questionnaire and patient satisfaction questionnaire were used to survey 126 orthopedic inpatients in a tertiary hospital in Jiangsu Province. Results The escort rate in June-July 2020 was significantly lower than that of the same period in 2019 (44. 57% vs 68. 26%, P=0. 001); whether there was family support during the hospitalization period did not affect patient satisfaction (F=1. 32, P=0. 182) ; Gender (t=3. 787, P<0. 001), occupation (t=2. 498, P=0. 014), and the impact of the epidemic on life (t=-2. 618, P=0. 010) are the main factors affecting satisfaction. Conclusion In the post-epidemic era, we still remains vigilant and never slacken our efforts to normalized prevention and control. It is necessary to pay more attention to the psychology of hospitalized male patients and reduce the impact of the epidemic on the lives of inpatients, so as to continuously optimize medical services, ensure medical safety, and improve patient satisfaction. (目的 调查后疫情时代骨科病房护理管理下住院患者探陪现状及满意度情况, 为现有形势下如何兼顾患者探陪需求, 提升患者满意度及医疗工作安全开展提供参考。方法 采用一般情况调查表和患者满意度调查表, 对江苏省某三甲医院126名骨科住院患者进行调查。结果 2020年6月—7月住院患者陪护率与2019年同期相比明显降低(44. 57% vs. 68. 26%, P=0. 001); 住院期间是否有家人陪护不影响患者的满意度(F=1. 32, P=0. 182); 性别(t=3. 787, P＜0. 001)、职业(t=2. 498, P=0. 014)、疫情对生活的影响(t=-2. 618, P=0. 010)是影响满意度的主要因素。结论 后疫情时代, 常态化防控不松懈, 需更加关注男性住院患者的心理健康, 减少疫情对住院患者生活带来的影响, 从而不断优化医护服务, 保障医疗安全, 提升患者满意度。)